1991
DOI: 10.1177/036354659101900402
|View full text |Cite
|
Sign up to set email alerts
|

Arthrofibrosis in acute anterior cruciate ligament reconstruction

Abstract: Arthrofibrosis is a potential complication of acute ACL reconstruction. Arthrofibrosis prevents the patient from regaining full range of motion, particularly the terminal 5 degrees of full extension, postoperatively. We did a retrospective study of 169 acute ACL reconstructions in a population of young athletes (average age, 22 years). We sought to determine the optimal time to perform acute ACL reconstruction with respect to arthrofibrosis and the effects of an accelerated versus conventional rehabilitation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
148
2
5

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 574 publications
(176 citation statements)
references
References 15 publications
7
148
2
5
Order By: Relevance
“…Deficits in flexion and extension ROM are related to tunnel placement, roof impingement and timing of surgery [9,11,21,24,31]. In the reported method, we fixed the graft in 30 deg of flexion, whereas most authors now recommend fixation of the graft with the joint in neutral position.…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in flexion and extension ROM are related to tunnel placement, roof impingement and timing of surgery [9,11,21,24,31]. In the reported method, we fixed the graft in 30 deg of flexion, whereas most authors now recommend fixation of the graft with the joint in neutral position.…”
Section: Discussionmentioning
confidence: 99%
“…Patients need prolonged physical therapy and frequently require surgical intervention. 1,4,15,20 The surgical treatment of arthrofibrosis is demanding and requires familiarity with arthroscopic debridement techniques 2, 4,9,10,13,15,17,19,20 and, in some cases, anterior and posterior arthrotomy approaches. 1,7,14,22 Lysis of adhesions surgery has been shown to significantly improve knee motion ; however, final functional results are compromised, and there is a high incidence of degenerative changes seen radiographically.l,14 Concern has been expressed over loss of motion and subsequent abnormal knee kinematics leading to degenerative articular changes.~° 1~ Further study is needed to evaluate the progression of degenerative changes in these patients.…”
mentioning
confidence: 99%
“…12 The timing of surgery has been shown by numerous authors to correlate with postoperative motion. Several authors have found an association between early surgery and subsequent arthrofibrosis, 13,14 whereas others have found no relationship between loss of motion and acute ACL reconstruction. 15,16 Most investigators believe that too much emphasis has been placed on a specific period of time between injury and surgery.…”
Section: Preoperative Factorsmentioning
confidence: 99%